Single Commercially Available Integrated Circuit-based Sinusoidal Oscillators with Amplitude Adjustability and Electronic Control of Condition - Duangkaew, Suleeporn; Supavarasuwat, Piya; Siripruchyanun, Montree; Sotner, Roman; Jaikla, Winai; Sunthonkanokpong, Wisuit (My University, 2024)
This paper presents four new sinusoidal oscillators using a commercially available integrated circuit (IC). The proposed circuits are simple topologies that employ a single commercial IC, LT1228. It is connected to passive element, consisting of four resistors and two capacitors. All derived oscillator circuits have low output impedance, allowing them to connect to other circuits without requiring an additional buffer. Using an active LT1228 device enables electronic adjustment of parameters in the proposed circuits. A feedback resistor can be used to change the output signal's amplitude without affecting the oscillation's frequency or condition. We performed both simulations using the PSPICE program and experiments to confirm the accuracy of all proposed oscillator circuits. The best total harmonic distortion was 0.13% for the proposed oscillator circuit 3. Adjusting the maximum amplitude using a resistor provides a gain of roughly 1.5–16.5 dB for the proposed oscillator circuit no. 1.
Keywords: Active building block; analog circuit; electronic Tune; LT1228; sinusoidal oscillator